2022
DOI: 10.3390/diagnostics12030747
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy: Preparation and Potential Complications

Abstract: Colonoscopy is a fairly common test that serves both diagnostic and therapeutic purposes. It has been considered the gold standard in colorectal cancer screening for several years. Due to the nature of the examination, various types of complications may occur. The purpose of this analysis is to describe the various complications related to the period of preparation for colonoscopy among hospitalized patients, including life-threatening ones, in order to know how to avoid complications while preparing for a col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…25,26 Nausea and vomiting, or even Mallory-Weiss syndrome, are the most frequent adverse reactions following the administration of a high dose of PEG. 27 We found that with less PEG volume, the patients' nausea was also relieved. The incidence rate of vomiting following administration of 3L and 2L PEG was significantly lower than that of 4L PEG.…”
Section: Discussionmentioning
confidence: 72%
“…25,26 Nausea and vomiting, or even Mallory-Weiss syndrome, are the most frequent adverse reactions following the administration of a high dose of PEG. 27 We found that with less PEG volume, the patients' nausea was also relieved. The incidence rate of vomiting following administration of 3L and 2L PEG was significantly lower than that of 4L PEG.…”
Section: Discussionmentioning
confidence: 72%
“…With the increase in colorectal cancer screening, a significant reduction in the incidence of COAD has been observed; however, the mortality is expected to reach 60% by 2035 [ 5 ]. It should be noted that despite advances in currently available standard treatments, e.g., surgery, chemotherapy, radiotherapy and immunotherapy, the 5-year overall survival (OS) of patients with COAD remains poor [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in colorectal cancer screening, a significant reduction in the incidence of COAD has been observed; however, the mortality is expected to reach 60% by 2035 [ 5 ]. It should be noted that despite advances in currently available standard treatments, e.g., surgery, chemotherapy, radiotherapy and immunotherapy, the 5-year overall survival (OS) of patients with COAD remains poor [ 5 , 6 ]. Therefore, there is an urgent need for the development of novel biomarkers to improve the outcome of patients, allowing earlier therapeutic intervention and reducing the increasing burden of COAD [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Factors that significantly influence the development of this type of malignancy include lifestyle, e.g., obesity, prolonged and frequent smoking, alcohol consumption and a diet low in fibre but rich in red meat. Other risk factors include the presence of chronic inflammatory bowel disease (IBD), inadequate exposure to sunlight, including vitamin D3 deficiency, and genetically determined changes leading to colonic mucosal cell dysplasia [2][3][4]. It should also be noted that CRC is a highly invasive type of cancer and shows a high level of heterogeneity.…”
Section: Introductionmentioning
confidence: 99%